2020
DOI: 10.2147/ott.s279798
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Intergenic Non-Protein Coding RNA 519 Promotes the Biological Activities of Tongue Squamous Cell Carcinoma by Sponging microRNA-876-3p and Consequently Upregulating MACC1</p>

Abstract: Long intergenic non-protein coding RNA 519 (LINC00519) promotes the development of lung squamous cell carcinoma. In this study, we detected the expression of LINC00519 in tongue squamous cell carcinoma (TSCC) and examined its clinical significance. Additionally, the regulatory effects of LINC00519 on behaviors of TSCC tumor cells were explored through functional experiments. Finally, mechanistic studies were performed to elucidate the molecular events underlying the tumor-promoting actions of LINC00519 in TSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…LINC00519 was overexpressed and related to a poor prognosis in lung squamous cell carcinoma (LUSC) patients, which promoted tumor progression via miR-450b-5p/miR-515-5p/YAP1 pathway ( Ye et al, 2020 ). Similarly, it was also demonstrated to stimulate tumor development through miR-876-3p/MACC1 axis by serving as an emulative endogenous RNA in patients with tongue squamous cell carcinoma (TSCC) ( Liu et al, 2020 ). And LINC01133, a widely reported carcinogenic lncRNA, was shown to exert promoting effects in multiple human malignancies, which was also associated with tumor proliferation and epithelial–mesenchymal transformation (EMT) in PC ( Huang et al, 2018 ; Liu and Xi, 2020 ; Zhai et al, 2020 ; Liu et al, 2021 ; Yin et al, 2021 ; Sun et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00519 was overexpressed and related to a poor prognosis in lung squamous cell carcinoma (LUSC) patients, which promoted tumor progression via miR-450b-5p/miR-515-5p/YAP1 pathway ( Ye et al, 2020 ). Similarly, it was also demonstrated to stimulate tumor development through miR-876-3p/MACC1 axis by serving as an emulative endogenous RNA in patients with tongue squamous cell carcinoma (TSCC) ( Liu et al, 2020 ). And LINC01133, a widely reported carcinogenic lncRNA, was shown to exert promoting effects in multiple human malignancies, which was also associated with tumor proliferation and epithelial–mesenchymal transformation (EMT) in PC ( Huang et al, 2018 ; Liu and Xi, 2020 ; Zhai et al, 2020 ; Liu et al, 2021 ; Yin et al, 2021 ; Sun et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long intergenic non-protein-coding RNA 519 (LINC00519) was first described in lung squamous cell carcinoma (LUSC) as an oncogene [96]. Localization analysis indicated that the vast majority of these lincRNA molecules can be found in the cytoplasm where they act as an miRNA-sequestering sponge [97]. In TSCC, one of those short RNAs is miR-876-3p, which was earlier widely described as aberrantly expressed and tumorigenic in many cancers [98].…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 99%
“…In TSCC, one of those short RNAs is miR-876-3p, which was earlier widely described as aberrantly expressed and tumorigenic in many cancers [98]. The study based on TSCC patients with high expression of LINC00519 demonstrated shorter overall survival and unsatisfactory prognosis [97]. Although the above lincRNA displays the potential to become an HNSCC biomarker, still a lot of work remains to be done.…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 99%
“…MiR-876-3p has been reported to be involved in the progression of various cancers, including breast cancer [ 13 ], ovarian cancer [ 14 ], and colon cancer [ 15 ]. A previous study have confirmed the role of miR-876-3p in NSCLC [ 16 ], but whether circTLK1 regulates miR-876-3p remains unclear.…”
Section: Introductionmentioning
confidence: 98%